MODERN TRENDS IN KYRGYS FOLK MUSICAL PERFORMING ART (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Kyrgyz folk traditional performing music has evolved over the centuries and conrinues to develop to this day. Traditional folk performing music is considered one of the most important and significant parts of the musical culture of the Kyrgyz people. This article discusses the modern way of development of the Kyrgyz folk traditional performing music over the years of independence, combintd with the life and aspirations of the people. Also, its main trends due to the modern way of developmebt are considered.
Keywords: folk traditional music, oral professional performance, tradition, pop music, trend, ideology, spiritual development, art, aesthetics.